Implementing Nonlethal Solutions for Free-Roaming Cat Management in a County in the Southeastern United States - Hamilton, Francis (Frontiers in Veterinary Science, 2019)
Abstract From 2006 to 2017, stray or free-roaming cats ranged from 38% to 54% of all animals going into the public shelter in Hillsborough County, Florida. Shelter overcrowding of cats, including free-roaming, feral, or community cats, is a major problem in parts of the world. Issues with free-roaming cats include the welfare of the cats themselves, public health and zoonotic diseases, spread of diseases to other species or pet cats, public nuisance, and predation of wildlife. Animal control is a government function and ultimately a taxpayer issue. This paper describes three methods of humane, nonlethal management of free-roaming cat populations that were successfully applied in Hillsborough County, Florida: low-income spay/neuter vouchers; small- and large-scale trap, neuter, vaccinate, and return (TNVR); and return to field (RTF). The methods used were contrary to the long-accepted practice of using euthanasia to control cat populations and generated opposition among certain stakeholders. While the human population of the county increased by 14.6% from 2010 to 2017, the methods used to control free-roaming cats assisted in achieving a 51% decrease in intake since 2007 and increased the live-release rate to 81.8% of cats taken in at the Pet Resources Center in 2017. This paper examines how this change in intake was achieved despite opposition to these programs. Keywords: Free-roaming cat management, TNVR, animal control and management, nonlethal methods of animal control, social change for animals